2014
DOI: 10.1111/bph.12769
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of hydrogen sulfide with myeloperoxidase

Abstract: BACKGROUND AND PURPOSEThe actions of hydrogen sulfide in human physiology have been extensively studied and, although it is an essential mediator of many biological functions, the underlying molecular mechanisms of its actions are ill-defined. To elucidate the roles of sulfide in inflammation, we have investigated its interactions with human myeloperoxidase (MPO), a major contributor to inflammatory oxidative stress. EXPERIMENTAL APPROACHThe interactions of sulfide and MPO were investigated using electron para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 77 publications
0
60
0
2
Order By: Relevance
“…Much more recently, it was shown that other ferric heme proteins can react directly with H 2 S to give an Fe III -SH complex with the same spectral changes observed in the initial study by Keilin [19,20]. One of the most studied of all H 2 S-heme protein interactions is that of H 2 S with a hemoglobin of the bivalve mollusc, Lucina pectinata , that inhabits H 2 S-rich environments [for example, 21-26].…”
Section: The Biological Chemistry Of H2smentioning
confidence: 77%
See 1 more Smart Citation
“…Much more recently, it was shown that other ferric heme proteins can react directly with H 2 S to give an Fe III -SH complex with the same spectral changes observed in the initial study by Keilin [19,20]. One of the most studied of all H 2 S-heme protein interactions is that of H 2 S with a hemoglobin of the bivalve mollusc, Lucina pectinata , that inhabits H 2 S-rich environments [for example, 21-26].…”
Section: The Biological Chemistry Of H2smentioning
confidence: 77%
“…The mechanism by which excess H 2 S facilitates reduction of the ferric-H 2 S complex (or ferric-HS − complex) is intriguing and has recently been demonstrated for myeloperoxidase (MPO) using spectroscopic measurements on the Fe II -sulfide complex, which was also independently synthesized by the reaction of reduced MPO with sulfide [20]. The sulfur-containing product of this reaction has been proposed to be dihydrogen persulfide (H 2 S 2 ) [26].…”
Section: The Biological Chemistry Of H2smentioning
confidence: 99%
“…The product of cytochrome c oxidase reduction under aerobic conditions has not been characterized but is predicted to be elemental sulfur 93,94 . Sulfide binds to the heme iron in myeloperoxidase 95 and lactoperoxidase 96 . Although it has been observed that re-formation of the iron–sulfide complex of myeloperoxidase from compound I is oxygen dependent, possible sulfide oxidation products were not characterized 95 .…”
Section: Metal-catalyzed H2s Oxidation: Another Source Of Rss?mentioning
confidence: 99%
“…H 2 S also binds and reduces cytochrome c, a reaction that in the presence of oxygen leads to superoxide production (Wedmann et al 2014). In addition, Pálinkás et al (2014) have recently investigated interactions of H 2 S with human myeloperoxidase (MPO), a major contributor to inflammatory oxidative stress, to show that H 2 S inhibits the enzyme by reducing iron centre and by binding to the reduced Fe 2+ . It is still, however, unclear to which extent is the coordination and/or reduction of metal centres involved in signalling by H 2 S. Miljkovic et al (2013) demonstrated that metal centres in mitochondria are responsible for the H 2 S-stimulated haem centre-catalysed reduction of nitrite, a reaction which can explain the use of nitrite as an antidote for acute H 2 S poisoning.…”
Section: Reactions With Metal Centresmentioning
confidence: 99%